Tympanic membrane cholesteatoma: a rare finding - Atmaca, Sinan; Seçkin, Ender; Koyuncu, Mehmet (The Turkish Journal of Pediatrics, 2010)
We report a rare finding of tympanic membrane cholesteatoma in a two-year-old girl. Tympanic membrane cholesteatoma without trauma or surgery to the ear is a rare entity, with few cases documented in the literature. The exact etiology of this lesion is still unclear. The presentation, clinical course and management are discussed. A whitish spot on the tympanic membrane should raise suspicion for cholesteatoma. Early diagnosis and treatment are imperative to allow an easy removal and avoid middle ear involvement.